Bone box a Decker/Lazarus novel - Kellerman, Faye (New York, NY William Morrow, an imprint of HarperCollinsPublishers, 2017)
On a bright and crisp September morning, while walking a bucolic woodland trail, Rina Decker stumbles upon human remains once buried deep beneath the forest grounds. Immediately, she calls her husband, Peter, a former detective lieutenant with LAPD, now working for the local Greenbury Police. Within hours, a vista of beauty and tranquility is transformed into a frenetic crime scene. The body has been interred for years and there is scant physical evidence at the gravesite: a youthful skeleton, a skull wound and long dark strands of hair surrounding the bony frame. As Decker and his partner, Tyler McAdams, further investigate, they realize that they're most likely dealing with a missing student from the nearby Five Colleges of Upstate - a well-known and well-respected consortium of higher learning where Rina works. And when more human remains are found in the same area, Decker and McAdams know this isn't just a one-off murder case. Short-staffed and with no convenient entry into the colleges, Decker enlists Rina's help to act as the eyes and ears of campus gossip. Winding their way through a dangerous labyrinth of steely suspects and untouchable academics, Decker, McAdams, and Rina race to protect their community from a psychopathic killer still in the area - and on the hunt for a fresh victim.
104753
Keywords: Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Police -- New York (State) -- Fiction; Police spouses -- Fiction; Murder -- Investigation -- Fiction; New York (State) -- Fiction; Detective and mystery fiction; Mystery fiction